2003
DOI: 10.1051/forest:2003056
|View full text |Cite
|
Sign up to set email alerts
|

Response of newly planted Norway spruce seedlings to fertilization, irrigation and herbicide treatments

Abstract: -The effect of herbicide, fertilization and irrigation treatments on growth of planted Norway spruce seedlings were investigated in an experiment established in 1998 in southern Sweden. After three years, the amount of ground vegetation was about the same in fertilized, irrigated and fertilized + irrigated plots, but the amount was about double as in the control. Seedling growth was positively affected by the herbicide treatment. Fertilization increased growth when it was combined with herbicides. Irrigation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
4
14
0
1
Order By: Relevance
“…Although we did not measure moisture availability, this site is likely to experience droughty conditions during the growing season and we hypothesize that the positive volume responses were a result of improved soil moisture availability. Similar to other studies, our findings indicate that, the primary benefit from VC may be nutritional or moisture related depending on individual site conditions [21,23]. In future studies, it would be interesting to examine VC and fertilization responses where fertilization included, in addition to N and P, a broader selection of nutrients that may be limiting (e.g.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although we did not measure moisture availability, this site is likely to experience droughty conditions during the growing season and we hypothesize that the positive volume responses were a result of improved soil moisture availability. Similar to other studies, our findings indicate that, the primary benefit from VC may be nutritional or moisture related depending on individual site conditions [21,23]. In future studies, it would be interesting to examine VC and fertilization responses where fertilization included, in addition to N and P, a broader selection of nutrients that may be limiting (e.g.…”
Section: Discussionsupporting
confidence: 65%
“…More recently studies have reported significant growth gains relative to check for VC and fertilization applied singly and when combined for applications at the time of planting [4,18,[21][22][23]. Powers and Reynolds found that in P. ponderosa systems with extended summer droughts and infertile soils the primary limitation to growth was first soil moisture availability and secondarily nutritional limitations [23].…”
Section: Introductionmentioning
confidence: 99%
“…3) also responded positively to irrigation and fertilization applications. These conclusions are in agreement with previous studies related to growth, volume, and biomass production as related to fertilization and irrigation in various conifers species under field conditions (Nilsson and Orlander, 2003;Snowdon and Benson, 1992;Trichet et al, 2008). Maintaining high soil moisture in highly irrigated plots allows stomata to remain opened longer resulting in more volume growth (Albaugh et al, 2008).…”
Section: Effect Of Resource Availability On Growthsupporting
confidence: 82%
“…It is also possible that high root egression ability of growing seedlings has a more pronounced effect on the maintenance of seedling water balance if, contrary to the present study, soil water content is high at the beginning of the drought period. Finally, it must be remembered that the results from this study are not directly applicable to actual forest site, where newly planted seedlings have to compete with ground vegetation for water and nutrients [23,30].…”
Section: Discussionmentioning
confidence: 99%